Speaking with confidence - Gold, Nick. (UK : Penguin Business, 2020)
Does the thought of delivering a presentation make your heart skip a beat? Do your pitches fall flat, no matter how much preparation you put in? Are you often comparing yourself to more eloquent speakers and wondering how they capture the room? At some point in our careers, we will need to speak in front of an audience; whether to present our ideas to a group of five in a meeting, pitch for investment in front of a panel, or deliver a keynote speech to one thousand delegates.
Keywords: Public speaking; Self-confidence